Intraspecific variation of the green turtle, chelonia mydas (cheloniidae), in the foraging area of gorgona natural national park (colombian pacific) (2014)
The size distribution and body condition of the two morphotypes of green turtle (Chelonia mydas) foraging in Gorgona Natural National Park (GNNP) in the Colombian Pacific was assessed from 2003 to 2012. Measurements of straight carapace length (SCL), curved carapace length (CCL), weight, and body condition of 1,023 turtles captured on the GNNP reefs were recorded. More black turtles (n = 747) than yellow turtles (n = 276) were captured, all of them juveniles. Black turtles were significantly larger and heavier than yellow turtles. The size of recruitment to the neritic zone was 40.0-49.9 cm SCL for both morphotypes, but there were more yellow than black turtles in this size class, indicating a difference in the recruitment pattern. The body condition index of yellow turtles was significantly higher than that of black turtles, which could indicate differences in resource use. Based on our results, we suggest that GNNP might function as a recruitment area for yellow turtles, which arrive at smaller sizes and as part of a coastal migratory route for black turtles, which arrive at larger sizes and maintain residence at this location for an unknown period of time.Variación intraespecífica de la tortuga verde Chelonia mydas (Cheloniidae) en el área de forrajeo del Parque Nacional Natural Gorgona (Pacífico colombiano)Se comparó la distribución de tallas y condición corporal de los dos morfotipos conocidos de tortuga verde (Chelonia mydas) en el área de forrajeo del Parque Nacional Natural Gorgona (PNNG) en el Pacífico colombiano entre 2003 y 2012. Se tomaron medidas de largo recto de caparazón (LRC), largo curvo de caparazón (LCC), peso y condición corporal de 1.023 tortugas capturadas en los arrecifes del PNG. Se capturaron más tortugas negras (n = 747) que amarillas (n = 276), todas juveniles. Las tortugas negras fueron significativamente más grandes y pesadas que las amarillas. El tamaño de reclutamiento a la zona nerítica fue de 40,0–49,9 cm para ambos morfotipos, pero hubo más tortugas amarillas que negras en este intervalo de tamaños, lo cual sugiere una variación en el patrón de reclutamiento. El índice de condición corporal de las tortugas amarillas fue significativamente más alto que el de las tortugas negras, lo cual podría indicar diferencias en la utilización de recursos. Con base en los resultados obtenidos, se sugiere que el PNNG podría funcionar como un área de reclutamiento para las tortugas amarillas, las cuales llegan más pequeñas a esta zona; y como parte de la ruta migratoria costera de las tortugas negras, las cuales llegan más grandes e incluso residen en esta localidad durante un lapso de tiempo desconocido.